The Worst Thing, That was the Best Thing, That Ever Happened to Me (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
At age thirty, I was diagnosed with hereditary rheumatoid arthritis and informed by my rheumatologist that due to the disease, my police and sport careers were over. Thus, began a transition from policing to psychology. I reflect on my journey through the eyes of an existentially oriented psychologist and how these experiences inform my current practice with clients experiencing similar concerns.
Keywords: Rheumatoid arthritis; transitions; chronic pain; acceptance; identity; Spinelli; self-disclosure; disturbances With many thanks to Professor Ernesto Spinelli; for the comfort; friendship and guidance you have given me along the journey.